Makna Simbolik Dalam Tembang Ilir-Ilir Karya Sunan Kalijaga Dan Relevansinya Dalam Pendidikan Karakter Anak - Himatul Istiqomah (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
This research aimed to reveal the value of character education hidden behind the beautiful and highly symbolic string of words behind the phrase “bocah angon” and the verb “angon” in the song Ilir-Ilir by Sunan Kalijaga. This was a descriptive qualitative research. The primary data source in this study was Tembang Ilir-Ilir by Sunan Kalijaga. While the secondary data sources were in the form of theories and result of previous researches related to the value of character education and semiotic analysis in literary works and other literature. Data collection in this study was carried out using the library research method and then analyzed using content analysis techniques. The results of this study indicated that in the song Ilir-Ilir, there was a phrase that is very symbolic and has a very broad interpretation, namely Bocah Angon, a shepherd boy. It was a symbol of the authenticity of a true leader, who can nurture, protect, and prosper the nation with his tenacity and wisdom. Besides that, there was also the verb angon, which is the work of herding which can provide character education to the figure of a leader related to adaptation strategy to survive through natural selection and train irritability through direct contact with nature so that they can map the field well. The results of this study can be used as a reference for character education to be emulated by the next generation of the nation from an early age.